Determinación de la prevalencia de anemia ferropénica en la población femenina de la parroquia El Cisne del cantón Loja. - Cueva Nugra, Tatiana de Lourdes (2014)
According to the World Health Organization, anemia is the most common and widespread nutritional disorder in the world. The present study aims to determine the prevalence of iron deficiency anemia in 300 women older than 13 years old in El Cisne parish, Loja canton. For that, it was applied a survey, which contained anthropometric data, dietary habits and characteristics of menstrual period. In the iron deficiency anemia evaluation the blood parameters analyzed were: serum ferritin, hematocrit, hemoglobin and red cell indices. Prevalence of iron deficiency anemia obtained was 25.3%, predominantly in women of childbearing age with 71.1%. According to body mass index the 64.5% of women presented an ideal weight. Through surveys, it was determined the possible causal factors of iron loss, predominating poor nutrition and prolonged menstruation, with 65.9%, followed by 61.9%, respectively. Additionally it was provided educational talks about the importance of proper nutrition, with the purpose to reduce prevalence of iron deficiency anemia, due it remains a public health problem that requires attention.